Analisis Kebutuhan Pengembangan Project Based Teaching Module untuk Meningkatkan Kreativitas Siswa SMK Pariwisata Dwi Tunggal - I Gusti Ayu Agung Sinta Diarini; I Made Ari Winangun; I Putu Pranatha Sentosa; Ni Made Erpia Ordani Astuti (Jurnal Penelitian Agama Hindu, 2022)
The teaching module is a concrete form of learning planning in the implementation of an independent curriculum. Therefore, teaching modules are needed to facilitate the student learning process. This is the basis for proposing a study to describe needs analysis in the development of project based teaching modules. This type of research is descriptive which aims to describe the needs analysis for the development of a project based teaching module to increase the creativity of students of Dwi Tunggal Tourism Vocational School. The subjects of this study were 59 students of class X of the Culinary Study Program and 4 teachers of culinary sciences. Sources of data in this study in the form of primary data through the technique of giving questionnaires and secondary data through the analysis of the Culinary Basics learning program. Data analysis techniques in this study were carried out by data reduction, data presentation, and triangulation based on some relevant literature. The results of this study indicate that the development of a project based teaching module to increase the creativity of students at the Dwi Tunggal Tabanan Tourism Vocational School is very much needed by teachers and students as an effort to overcome some problems in the learning process. This module has a project implementation basis in its learning which consists of 8 scopes of material in the odd semester Culinary Basics subject and has a structure in the form of general information, core components, and attachments according to the pocket book for the development of independent curriculum teaching modules. In accordance with the results of the needs analysis, further efforts are recommended as a follow-up to the findings in this study. These efforts are: (i) designing a project based teaching module (blueprint) design; (ii) developing project based teaching modules to facilitate student learning processes; and (ii) testing the effectiveness of the implementation of the project based teaching module in accordance with the expected instructional impact.